Pemanfaatan Sampah Organik untuk Produksi Pupuk Kompos Berkualitas: Inovasi Kolaboratif Fakultas Teknik USK untuk Meningkatkan Pendapatan dan Daya Saing Mitra Usaha - Mulana, Farid; Azwar, Azwar; abubakar, abubakar; Hisbullah, Hisbullah; Hasrina, Cut Delsie (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2024)
The community service activity conducted at the Faculty of Engineering, Syiah Kuala University, is aimed at increasing income and competitiveness through the production of compost fertilizer from organic waste. This activity involves three independent business partners, namely the Student Executive Board of the Faculty of Engineering, the Atsiri Research Center, and Violet Garden. The background of this community service activity is the existence of problems faced by each partner in their respective fields of business, such as limited funds, utilization of waste, and product marketing. The purpose of this activity is to provide a collaborative innovation solution that can improve the quality of products, knowledge, and skills of the partners. The method of this activity is by designing and making a raw material shredder, a compost fertilizer production place, supporting tools, workshops and training, packaging techniques, and marketing strategies. The results of this activity are the creation of quality compost fertilizer products, increased knowledge and skills of the partners, and increased income and competitiveness of the partners. It is expected that this community service activity can contribute to the development of technology and community science, especially in the field of organic waste management into compost fertilizer.